2014
DOI: 10.1002/anie.201406415
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I) Catalysis at Extreme Concentrations Inside Self‐Assembled Nanospheres

Abstract: Homogeneous transition-metal catalysis is a crucial technology for the sustainable preparation of valuable chemicals. The catalyst concentration is usually kept as low as possible, typically at mM or μM levels, and the effect of high catalyst concentration is hardly exploited because of solubility issues and the inherent unfavorable catalyst/substrate ratio. Herein, a self-assembly strategy is reported which leads to local catalyst concentrations ranging from 0.05 M to 1.1 M, inside well-defined nanospheres, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 52 publications
3
86
0
Order By: Relevance
“…Subsequently, we decided to perform the co-assembly of 1 and less bulky bis(pyridine) ligand 2 in a 3:1 molar ratio. 14a,14b,22 When the mixture of 1 , 2 , HDA, and Pd(NO 3 ) 2 was heated in DMSO at 70 °C for 72 h we observed the quantitative formation of the cubooctahedral M 12 L 24 spherical complex MOP1 (Figure 1) in accord with the precedent of Fujita on related bis(pyridine) ligands. Although we depict MOP1 as being composed of an 18:6 ratio of ligands 1 and 2 , we believe that the stoichiometry represents a statistical distribution around the 18:6 ratio in accord with the results on two component assemblies previously prepared by Fujita.…”
Section: Introductionsupporting
confidence: 72%
“…Subsequently, we decided to perform the co-assembly of 1 and less bulky bis(pyridine) ligand 2 in a 3:1 molar ratio. 14a,14b,22 When the mixture of 1 , 2 , HDA, and Pd(NO 3 ) 2 was heated in DMSO at 70 °C for 72 h we observed the quantitative formation of the cubooctahedral M 12 L 24 spherical complex MOP1 (Figure 1) in accord with the precedent of Fujita on related bis(pyridine) ligands. Although we depict MOP1 as being composed of an 18:6 ratio of ligands 1 and 2 , we believe that the stoichiometry represents a statistical distribution around the 18:6 ratio in accord with the results on two component assemblies previously prepared by Fujita.…”
Section: Introductionsupporting
confidence: 72%
“…15 Molecular recognition, 6, 7 self-assembly, 8 lock-key modality 9 and reversibility 10 are among the most important features that enable supramolecular chemistry to be employed in many applications including catalysis, 11, 12 delivery, 13, 14 sensing, 1517 and imaging. 18 These applications use building blocks assembled together by intermolecular interactions including electrostatic interactions, 19 hydrogen bonding, 20 π–π interactions, 21 ion-dipole interactions, 22, 23 hydrophobic or solvophobic effects.…”
mentioning
confidence: 99%
“…Mechanistic hypotheses were supported through deuterium labeling studies. Gold catalysts inside self-assembled nanospheres were employed for enyne metathesis and other gold-catalyzed transformations [1194]. A DFT study of gold catalyzed cycloisomerization/enyne metathesis using yne-vinylidenecyclopropanes suggested that alkylidenecyclopropylcarbene complexes were likely not intermediates due to the high energy of these species [1195].…”
Section: )mentioning
confidence: 99%